Situation Report: Bulgaria, 20 April 1965 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Information on Sofia Conspiracy Todor Zhivkov on Volunteers in Vietnam New US Envoy to Sofia Appointed Another Trust Formed Joint Bulgarian-Hungarian Enterprise Scientific-Technical Association for Water Economy